KEANEKARAGAMAN JENIS BURUNG DI HUTAN KOTA BUMI PERKEMAHAN DAN GRAHA WISATA CIBUBUR - Wiranata, Ardi; Nitibaskara, Tb Unu; Muttaqin, Zainal (Jurnal Nusa Sylva, 2017)
Jamboree Campsite Cibubur (BUPERTA) is located on the outskirts of Cibubur City which provides good suitable for birds. This study aims to study the diversity of bird species and identify habitat characteristics. Methods used are counting method, MacKinnon type list, habitat profile creation and interview. Shannon-Wiener's diversity index is obtained with a value of 2.921in the high category of it in a region. Number of bird species recorded as many as 22 species of birds. Category of easy type meeting types such as types of coconut honey, bondol java, bird church, cucak kutilang. The use of some types of tree strata such as feeding location, playground or chatting with each other and resting location, but not always the birds use only one type of habitat but there are some birds that use some habitat type in their daily activities. is carried out to see how vegetation shape and environmental conditions become the observation plot. The result vegetation analysis was obtained the identified tree level is 9 species. This refers to the background of the urban forest area that was once a rubber plantation. Level of dominance type rubber (Hevea brasiliensis) amounted to 14 individuals. The Import Value Index (INP) of vegetation analysis for plant type pole level with highest INP value is rubber of 54.08%, while the second highest pole is eboni (Diospyros celebica) of 48.13%.